Development of Mixture "Clay – Electro-Smelting Slag" for Ceramic Brick; Applied Mechanics and Materials; Vol. 682 : Innovation Technology and Economics in Engineering - Torosyan V. F. Vera Fedorovna (Material Science, Machining Technologies and Equipments in Mechanical Engineering, 2014)
Title screen